PERBANDINGAN AKTIVITAS ANTIBAKTERI EKSTRAK DAUN SUNGKAI DAN DAUN TANJUNG TERHADAP Salmonella typhi IN VITRO - Emilia Zulaiha; Noor Muthmainah; Agung Biworo (Homeostasis, 2022)
Sungkai and Tanjung plants are often used by the community as traditional medicine. Extracts of sungkai leaf and tanjung leaf extract are known to contain active compounds that act as antibacterials such as alkaloids, flavonoids, saponins, tannins and others. This study aimed to analyze the comparison of the antibacterial activity of sungkai and tanjung leaf extracts against Salmonella typhi in vitro. This study was a true experimental study using the Posttest-Only With Control Group Design method with the treatment groups in the form of sungkai leaf extract and tanjung leaf extract with each test concentration of 25%, 50%, 75% and 100% and chloramphenicol 30μg as a positive control and aquadest as a negative control. Data were analyzed using One-Way ANOVA test, Post-hoc LSD and independent T-test. The results of the average diameter of the inhibition zone formed from concentrations of 25%, 50%, 75% and 100% of sungkai leaf extract on the growth of Salmonella typhi were 6.45 mm, 9.20 mm, 11.95 mm, 13.08 mm, respectively. and tanjung leaf extract of 12.70 mm, 15.42 mm, 17.46 mm, 19.20 mm. Based on the results of One-Way ANOVA statistical analysis, the value (p<0.05). The conclusion of this study was that there was a significant difference in the antibacterial activity of the extracts of sungkai and tanjung leaves against Salmonella typhi